The Fibonacci sequence \(F_n\) is given by

\(F_1 = F_2 = 1, F_{n+2} = F_{n+1} + F_{n} (n \in N)\)

Prove that

\(F_{2n} = \frac {F_{2n+2}^3 + F_{2n-2}^3}{9} - 2F_{2n}^3\)

for all \(n \geq 2\).

No vote yet

1 vote

×

Problem Loading...

Note Loading...

Set Loading...

## Comments

Sort by:

TopNewestWhere did you get all these proof problems? Were you inspired by a certain someone? :D

Log in to reply

A bit, but I have been making or finding these questions through the past weeks between school assignments. Finn, one of these questions were inspired by you. Guess which one. :D

Log in to reply

Which one?

Log in to reply

Log in to reply

Log in to reply

Log in to reply

Log in to reply